Borders in Attribution: On two Italian marble Reliefs Depicting Apostles from the Moscow Pushkin State Museum of Fine Arts Collection - Rastorguev, Vasily A. (Actual Problems of Theory and History of Art, 2019)
The paper concerns itself with two small marble reliefs depicting Apostles from the collection of Moscow State Pushkin Museum of Fine Arts. Previously unpublished, the reliefs present a problem from an attributional standpoint. Having entered the Moscow Museum collection in 1934, they have been traditionally ascribed to an unknown Italian master of the 16th century, probably Venetian. Their original provenance, destination and even iconography remain unclear. Several iconographic and stylistic details preclude the author from accepting the traditional attribution, while new data gathered on provenance and a comparison of the reliefs in question with the reliefs of the pulpit in Santa Maria Assunta in Nola, near Naples, present interesting results. The pulpit in Nola, created by Giovanni da Nola (1478–1559), a pupil of Benedetto da Maiano, constitutes the closest visual analogy to the Moscow reliefs, yet it was heavily restored in the late 19th century by an accomplished Neapolitan sculptor Salvatore Cepparulo. This fact makes a late Ottocento dating for the Moscow reliefs equally possible.